A 28 GHz GaAs front‐end IC with single positive supply voltage. Issue 4 (28th November 2020) - Park, Jeongsoo; Kim, Jeong‐Geun
Abstract: This paper presents 28 GHz GaAs front‐end IC for 5G beamforming systems with single positive supply voltage. A 28 GHz front‐end IC consists of a 3‐stage power amplifier, a 3‐stage low noise amplifier and two reflective type single pole double throw switches in 0.15 μm enhancement‐mode (E‐mode) GaAs pHEMT technology. The proposed 28 GHz front‐end IC is controlled only with single positive supply voltage. The measured front‐end IC Tx mode gain and Rx mode gain are 16.3 dB and 16.8 dB at 28 GHz, respectively. The achieved output P1dB and saturation power (PSAT ) in Tx mode are 18 dBm and 21 dBm, respectively. The achieved input P1dB and noise figure in Rx mode are −8 dBm and 3 dB, respectively. The 28 GHz GaAs front‐end IC consumes DC current of 216 mA in Tx mode at 4 V supply voltage and 20 mA in Rx mode at 2.5 V supply voltage. The proposed 28 GHz front‐end IC chip size is 2.5 x 2.2 mm 2 .